Leukocytoclastic vasculitis – three clinical cases - Raszeja-Kotelba, Barbara; Pietrzykowska-Fryca, Izabela; Czarnecka-Operacz, Magdalena; Żmudzińska, Maria (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2004)
Leukocytoclastic vasculitis is presented as purpuric exanthema caused by capillaries and venules inflammation with immune complexes formation. The histopathological examination reveals the inflammation changes of the vessels, fibrinoid exudation and cellular inflammatory infiltration with the perivascular leukocytoclasia. The disease may be manifested as cutaneous lesions only, or as serious systemic disorder. Different triggering factors, such as infections, drugs, chemical agents may initiate the formation of immune complexes. In other cases the triggers my be unknown. We present three clinical cases of classic course of leukocytoclastic vasculitis.